The Impacts of Credit Derivatives on Bank Portfolio Performance: An Empirical Analysis - Ma, Xiaosu (2012)
Following the 2007-2009 financial crisis, the debates on the effects of credit derivatives has become more widely and fierce. The key objective of this dissertation is to understand how credit derivatives can affect portfolio performance of banks, and empirically examine whether credit derivatives can improve portfolio performance and reduce bank earnings volatility during both non-crisis and crisis periods. To reach the research objective, two research questions are addressed: The primary question is does usage of credit derivatives improve bank portfolio performance? The secondary question is does hedging through credit derivatives reduce banks’ risk on return? The secondary is set to offer better answer for the primary question.